Association of microsatellite genotypes with layer economic traits in a selected strain of Rhode Island Red chicken - RAHIM, ABDUL; KUMAR, SANJEEV; DAS, ANANTA KUMAR; DEBNATH, JOWEL; YADAV, RAMJI; KRISHNAN, JAGADEESAN (The Indian Journal of Animal Sciences, 2023)
Randomly selected 76 pullets of RIR selected strain were screened for microsatellite polymorphs and investigated for their association with layer economic traits. Microsatellite alleles were separated from genomic DNA samples through 3.4% MetaPhor® agarose gel electrophoresis. Data were recorded on age at first egg (AFE), egg weights and egg production (EP) at certain age. Microsatellite analysis revealed nine polymorphic loci (EW) and genotypes at ADL0020 locus were significantly associated with EP at 40 and 64 weeks of age, CC (110 bp/110 bp) genotype had the highest EP, whereas, AD (126 bp/102 bp) and BD (118 bp/102 bp) genotypes recorded the lowest EP. Genotypes at ADL0023 locus were associated with AFE, EP at 40 weeks of age, CC (176 bp/176 bp) genotype followed by AB (202bp/188bp) genotype had earlier AFE, whereas, AC (202bp/176bp) genotype followed by BB (188bp/188bp) genotype demonstrated late AFE. ADL0210 locus had significant impact on AFE, egg weight at 28/40/64 weeks of age; BB (124bp/124bp) genotype followed by AA (132 bp/132 bp) genotype had earlier AFE than AB (132 bp/124 bp) genotype. Both AB and AA genotypes revealed significantly higher egg weight at 28/40/64 weeks of age than BB genotype. The BB (176 bp/176 bp) genotype followed by AB (192 bp/176 bp) genotype at MCW0014 locus revealed higher egg weight at 28 weeks of age in comparison to AA (192bp/192bp) genotype. Allele C (110 bp) at ADL0020 and A (132 bp) at ADL0210 either in homozygous or heterozygous condition were linked to the traits of egg weight and egg production performance, respectively. The results might impact on genomic selection aided poultry breeding programme.